Consumer Legal Protection Against Investment Practices Under the Guise of Hajj and Umrah: A Review of Law Number 8 of 1999 Concerning Consumer Protection - Ulipah Ulipah; Rois Harliyanto (Pusat Publikasi Nusantara, 2026)
This study aims to analyze the forms of legal protection for consumers and the legal liability of business actors in investment practices disguised as Umrah services, viewed from Law Number 8 of 1999 concerning Consumer Protection. This research employs a normative legal method with statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials. The results indicate that consumer protection in such practices consists of two forms, namely preventive protection through education, supervision, and transparency of information, and repressive protection through the imposition of sanctions and compensation for consumers. However, in practice, such protection has not been effectively implemented, as reflected in the case of PT Global Insani, which shows an imbalance between consumers and business actors as well as limitations in fulfilling consumer rights. The legal liability of business actors includes civil, administrative, and criminal responsibilities. Although normatively business actors are required to fully compensate consumer losses, in practice such responsibilities are often not optimally fulfilled. Therefore, strengthening supervision, law enforcement, and consumer awareness is necessary to achieve effective legal protection.